2000
DOI: 10.1021/ic000581t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Mixed LiLnX4(Ln = La, Dy; X = F, Cl, Br, I) Rare Earth/Alkali Halide Complexes

Abstract: The structure, bonding and vibrational properties of the mixed LiLnX4 (Ln = La, Dy; X = F, Cl, Br, I) rare earth/alkali halide complexes were studied using various quantum chemical methods (HF, MP2 and the Becke3-Lee-Yang-Parr exchange-correlation density functional) in conjunction with polarized triple-zeta valence basis sets and quasi-relativistic effective core potentials for the heavy atoms. Our comparative study indicated the superiority of MP2 theory while the HF and B3-LYP methods as well as less sophis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…At the same time, for the tridentate structure the degree of degeneracy is only four (according to the four sides of a tetrahedron). The different degrees of degeneracy of the bi-and tridentate forms have an influence on their relative abundance at high temperatures, as it was already suggested by Groen et al [28,29]. They showed that the equilibrium constant at high temperatures depends mostly on the entropy difference, S • (T), and not on which structure is actually more stable at zero Kelvin.…”
Section: Population Analysis Nbo Analysis Bondingmentioning
confidence: 69%
See 1 more Smart Citation
“…At the same time, for the tridentate structure the degree of degeneracy is only four (according to the four sides of a tetrahedron). The different degrees of degeneracy of the bi-and tridentate forms have an influence on their relative abundance at high temperatures, as it was already suggested by Groen et al [28,29]. They showed that the equilibrium constant at high temperatures depends mostly on the entropy difference, S • (T), and not on which structure is actually more stable at zero Kelvin.…”
Section: Population Analysis Nbo Analysis Bondingmentioning
confidence: 69%
“…Simple Hartree-Fock level computations have been performed together with mass spectrometric studies of NaCeCl 4 and NaNdCl 4 [14,15]. Later, Groen et al [27][28][29] studied the structures of LiLnX 4 (Ln = La, Ce, Dy; X = F-I) and MLaX 4 (M = Na, K, Cs; X = F-I) complexes at the MP2 and density functional levels. In this paper we report the structure, dynamics and thermodynamic properties of the NaDyBr 4 complex based on high-level computations.…”
Section: Introductionmentioning
confidence: 99%
“…The two-parameter set of f functions for La was taken from ref 24 La and the f polarization functions for Cl, Br, and I have been optimized in our previous study (exponents: R gLa ) 0.731; R fCl ) 0.720; R fBr ) 0.581; R fI ) 0.426). 19 The 2d and f functions for potassium and cesium were obtained in this study according to the procedure described in ref 28 (exponents: R dK ) 2.048, 0.512; R fK ) 1.174; R dCs ) 0.706, 0.1765; R fCs ) 0.610). For F the 6-311+G-(2df) and for Na the 6-311G(2df) basis sets were applied.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The electronic structure of molecular systems containing lanthanoid elements has been the object of numerous experimental [53,54] and theoretical [55][56][57][58][59][60][61][62] studies. In this framework, one of the most challenging topics is the "chemical" description of the lanthanoid-ligand or actinide-ligand interactions in terms of ionic versus covalent interaction [63][64].…”
Section: Lanthanoid Complex Catalyst For Ring Opening Reaction Of Metmentioning
confidence: 99%